FAO plant production and protection paper N.126 - I C Onwueme (FAO, 1994)
The document focuses attention on the significant role root crops in the economy of developing countries. It is intended to assit Government officails and policy makers in acquiring resources for research and development and is directed towrds Ministries of Planning and Agriculture, their advisers and donors. It points to the need for strengthening national policies to support research, training and extension programmes on a multipdisciplinary basis for the development of new technologies that can meet farmers' needs and consumer' demand.